(untitled) (Revista Contexto & Saúde, 2023)
Post-Covid-19 Syndrome is characterized by the persistence and/or appearance of new symptoms and abnormalities that persist beyond 12 weeks from the onset of acute Covid-19 and are not attributable to alternative diagnoses. Among the symptoms described in the literature regarding Post-Covid-19 Syndrome, musculoskeletal pain is among the most frequent. The present study aimed to review the literature and identify the form of presentation and predictive factors for musculoskeletal pain in Post-Covid-19 Syndrome. A comprehensive literature search was performed in the following databases: Medline (via PubMed), Embase, PEDro, Lilacs, Scopus, Web of Science and Cinahl from April 22 to June 14, 2022. Of the 2,044 articles found, 16 were included, comprising a total of 13,089 patients. The results showed that myalgia (27.12%, 11 studies), arthralgia (28.88%, 9 studies), arthromyalgia (43.07%, two studies) and musculoskeletal pain (15.3%, one study) were the pain musculoskeletal symptoms disorders present in Post-Covid-19 Syndrome. Female gender was a risk factor for the presence of arthralgia and myalgia in the Post-Covid-19 Syndrome, while age between 40 and 59 years was associated with persistence of arthromyalgia. And high body mass index (BMI) was a predictive factor for the presence of myalgia. The severity of the infection and the need for hospitalization were not predictors for the presence of myalgia and arthralgia in the Post-Covid-19 Syndrome. Future studies with a higher level of evidence and greater methodological rigor are encouraged.